DISTRIBUTION EXTENSION AND PARENTAL CARE IN LEPTODACTYLUS BREVIPES COPE, 1887 (ANURA: LEPTODACTYLIDAE) - Carrillo, Juan F. C.; Santana, Diego José; Prado, Cynthia P. A. [UNESP] (Universidad Nacional Autonoma de Mexico, 2022)
Parental care plays an important role in offspring survival in many amphibians, including frog species of the family Leptodactylidae. Here, we report a new locality of occurrence for Leptodactylus brevipes in the Brazilian Cerrado and describe its parental care behaviour. We observed a female of L. brevipes guarding a school of tadpoles and performing pumping behaviour. The tadpoles remained close to the attending female, scraping her legs and dorsal region several times. We did not record female aggressive behaviour. Our results agree with observations of maternal care in other species of the L. melanonotus group, such as L. melanonotus, L. natalensis, L. podicipinus, and L. pustulatus.
EXTENSIÓN DE DISTRIBUCIÓN Y CUIDADO PARENTAL EN LEPTODACTYLUS BREVIPES COPE, 1887 (ANURA: LEP-TODACTYLIDAE)
Keywords: Amphibia; parental investment; tadpole school